Visualization of colorectal neoplasia by a second-generation autofluorescence imaging system. (November 2013) - Ide, Daisuke; Tamai, Naoto; Inomata, Hiroko; Ohya, Tomohiko R; Aihara, Hiroyuki; Saito, Syoichi; Kato, Tomohiro; Tajiri, Hisao
Abstract Objective. Autofluorescence imaging (AFI) systems may allow better visualization of colorectal neoplasia than conventional methods. However, this is difficult to demonstrate objectively. Recently, a second-generation AFI system with a noise-reduction algorithm was developed. We aimed to objectively evaluate the visualization of colorectal neoplasia by using a second-generation AFI system and software to calculate the color-contrast index. Material and methods. We retrospectively reviewed 53 consecutive colorectal neoplasias examined using the second-generation AFI system. Color-contrast indices between the colorectal lesions and the surrounding normal mucosa in the WLI, AFI and NBI images were calculated. The WLI, AFI, NBI and CE images were also evaluated by endoscopists using questionnaire-based visualization scores. Results. The color-contrast index seen in the AFI images (33.74 ± 9.20) was significantly higher than that in either the WLI (11.14 ± 6.14) or NBI images (11.72 ± 7.12). There was no significant difference between the color-contrast indices of the WLI and NBI images. The mean AFI image visualization score (6.7 ± 1.8) was significantly higher than that of WLI (6.0 ± 1.7), and tended to be higher than that of the NBI images (6.1 ± 1.6) when assessed by less-experienced endoscopists. Conclusions. This study objectively demonstrates that compared to WLI and NBI, the second-generation AFI system enables superior visualization of colorectal neoplasms. The visualization scores were higher for the AFI images when evaluated by less-experienced endoscopists. These results indicate that the second-generation AFI system may aid less-experienced endoscopists in the detection of colorectal neoplasia.